Evaluating China’s Belt and Road Railway Projects in Nigeria: Infrastructure Gains and Strategic Risks - Gbadebo, Adedeji Daniel (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
China's Belt and Road Initiative (BRI) has had a substantial impact on Nigeria's infrastructure development, notably railway projects. This report evaluates the risks and advantages of BRI-funded railway projects, with a focus on the economic, social, and environmental implications. Utilizing a structured survey of 300 respondents from the Federal Capital Territory and Keffi in Nasarawa State, and analyzed using chi-square statistical methods, the research evaluates both the perceived benefits and associated risks of BRI-funded railway projects. While BRI railway investments improve transportation infrastructure, economic activity, and regional connections, questions remain about debt sustainability, reliance on Chinese technology and labor, and governance transparency. Statistical finings shows that the claimed advantages of BRI railway projects have no statistically meaningful influence on Nigeria's infrastructure development. Furthermore, the related dangers, such as increased national debt and economic reliance, are not much greater than the advantages. The study highlights critical policy implications, including the need for renegotiated BRI terms to enhance local enterprise participation, rigorous cost-benefit assessments before loan engagements, and strengthened governance frameworks to ensure transparency and accountability. It also underscores the importance of long-term maintenance strategies and robust environmental impact assessments to preserve infrastructure functionality and mitigate adverse outcomes. Furthermore, long-term maintenance plans and environmental impact assessments should be addressed in order to maintain infrastructure efficiency and reduce negative consequences. These insights contribute to ongoing discourse on infrastructure governance and development financing in emerging economies, underscoring the necessity of context-sensitive policy approaches that balance international cooperation with domestic capacity-building and institutional integrity.